ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJAPROFITABILITAS BANK PERKREDITAN RAKYAT KONVENSIONAL DIPROVINSI RIAU DENGAN EFISIENSI SEBAGAI FAKTOR PEMODERASIEL - AZWAN, VIRA; HASAN, AMIR (Jurnal Tepak Manajemen Bisnis, 2016)
This research analyze factors affecting the ability of conventional rural bank in RiauProvince in attaining profitability (Return On Asset) applying the efficiency asmoderating factor throughout the year 2010 to 2014. Factors that are taken into aconsideration for this research are Capital Adequacy Ratio (CAR), Loan to DepositRatio (LDR), and Non-Performing Loan (NPL)while Efficiency (BOPO) take on as amoderating variable. The purpose of this research is to identify the influence ofCapital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Non PerformingLoan (NPL) towards Return on Asset (ROA) and to ascertain efficiency as amoderating variable. As the object of this research, 16 conventional rural banks inRiau Province were selected by Purposive Sampling method and the data wascollected throughout the year 2010 to 2014. In order to get the required information,data collection was performed through documentation. Technical data was analyzedby Moderated Regression Analysis (MRA), to define the influence of CAR, LDR, NPLtowards ROA with BOPO as a moderating factor. The outcome of the analysisshowed the financial ratio which are CAR and LDR lack of significant effect to ROA,while NPL carried negative significant effect to ROA, subsequently BOPO was notjustified as a moderating variable. Predictive ability of the three variables on ROAwas 16.9% as shown by the adjusted R-square of 0.169.